Formulation and Development of Transferrin Targeted Solid Lipid Nanoparticles for Breast Cancer Therapy - Bhagwat, Geeta S.; Athawale, Rajani B.; Gude, Rajeev P.; Md, Shadab; Alhakamy, Nabil A.; Fahmy, Usama A.; Kesharwani, Prashant (Frontiers in Pharmacology, 2020)
Breast cancer is conventionally treated by surgery, chemotherapy and radiation therapy followed by post operational hormonal therapy. Tamoxifen citrate is a best option to treat breast cancer because its selective estrogen receptor modulation activity. Owing to its antiestrogenic action on breast as well as uterine cells, Tamoxifen citrate shows uterine toxicity. The dose 20 mg per day of Tamoxifen citrate required to show therapeutic effect causes side effects and toxicity to vital organs such as liver, kidney and uterus. In the present study, transferrin-conjugated solid lipid nanoparticles (SLNs) were successfully prepared to enhance the active targeting of tamoxifen citrate in breast cancer. Developed formulations were evaluated for particle size, surface charge, surface morphology and in vitro dissolution studies. Developed formulations exhibited more cytotoxicity as compared to pure Tamoxifen citrate solution in time as well as concentration dependent manner on human breast cancer MCF-7 cells. Further, cell uptake and flow cytometry studies confirmed the qualitative uptake of developed D-SLN and SMD-SLN by human breast cancer MCF-7 cells. Overall, proposed study highlights that transferrin engineered nanocarriers could enhance the therapeutic response of nanomedicines for breast cancer treatment.